Peran Wakaf dalam Membantu Pemulihan Ekonomi Nasional - Sobiyanto, Ahmad; Fatwa, Nur; Huda, Nurul (Badan Wakaf Indonesia, 2023)
Waqf, as an instrument of Islamic philanthropy, has great potential to play a strategic role for the Indonesian economy. The Covid-19 pandemic as a global pandemic has had an impact on various sectors in Indonesia. National Economic Recovery (PEN) is a government program in an effort to restore post-pandemic economic conditions in 6 sectors, namely Health, Social Protection, Business Incentives, MSME Support, Corporate Financing, and Local Government and Corporate Sectors. This study describes the role of waqf in helping the national economic recovery (PEN) in the six sectors. A qualitative research approach is used as this research method with documentary data collection techniques. Data sources in this study refer to texts derived from books, journals, and publications from related sources. The results of this study show that waqf, in various schemes, plays a role in assisting the PEN program in 6 sectors. In the health sector, waqf is implemented in the form of health facilities and services programs. In the Social Protection sector, waqf is implemented in the form of basic food and cash social assistance. In the field of Business Incentives, waqf is manifested in the form of a waqf nazir stimulus. In the field of MSME Support, waqf is implemented in capital assistance, production equipment, and assistance. In the field of Corporate Financing, waqf plays a role in storing funds in the waqf sukuk scheme / CWLS (SWR). In the field of Local Government and Corporation, waqf is implemented in the management of halal tourism and waqf cities.